Molecular characterization of carbapenem-resistant and carbapenem-sensitive Acinetobacter baumannii isolates from an intensive care unit in Ningbo, China - Chen, Xinwei; Tu, Yanye; Wang, Feng; Li, Hong; Zhao, Yujie; Jiang, Min; Gao, Hui; Zhang, Wei (Frontiers in Microbiology, 2025)
ObjectiveThis study aims to examine the variations in resistance genes, virulence genes, and drug susceptibility between carbapenem-resistant and carbapenem-susceptible Acinetobacter baumannii (CR-AB and CS-AB). Additionally, it seeks to assess the influence of efflux pump inhibitors on drug susceptibility, in order to provide new antimicrobial treatment strategies for CR-AB infections in the intensive care unit (ICU).MethodsA retrospective study was undertaken involving 39 A. baumannii (A. baumannii) strains isolated from the ICU of Li Huili Hospital, affiliated with Ningbo University, during the period from January to December 2023. Of these strains, 18 were classified as CR-AB and 21 as CS-AB. The minimum inhibitory concentrations (MICs) of commonly employed clinical antibiotics, polymyxin B, tigecycline, and ceftazidime/avibactam, were assessed using the microdilution method. The alterations in MICs of ceftazidime/avibactam for CR-AB isolates were evaluated before and after the incorporation of the efflux pump inhibitor phenylalanine-arginine-β-naphthylamine (PAβN). Whole genome sequencing (WGS) was conducted to elucidate the differences in resistance and virulence genes, and phenotypic validation of these virulence gene differences was performed utilizing the Galleria mellonella larvae model.ResultsThe CR-AB isolates demonstrated substantial resistance to ceftazidime, cefepime, ceftriaxone, ampicillin/sulbactam, tobramycin, gentamicin, and levofloxacin, while exhibiting moderate resistance to trimethoprim-sulfamethoxazole and amikacin. Conversely, the CS-AB isolates remained susceptible to all the aforementioned commonly utilized clinical antibiotics. Antimicrobial susceptibility testing indicated that 2.56% of the 39 A. baumannii strains displayed resistance to polymyxin B, with no resistance detected against tigecycline. The minimum inhibitory concentration (MIC) ranges for polymyxin B, tigecycline, and ceftazidime/avibactam were 0.125 μg/mL to 4 μg/mL, 0.25 μg/mL to 1 μg/mL, and 2/4 μg/mL to 256/4 μg/mL, respectively. PAβN was observed to reduce the MIC values of ceftazidime/avibactam against CR-AB in a concentration-dependent manner. Relative to the CS-AB isolates, the CR-AB isolates not only exhibited a more complex resistance gene profile but also showed greater diversity and abundance in their virulence gene profiles. The survival rate of CR-AB isolates was significantly lower in the G. mellonella larvae model, indicating that CR-AB strains from the ICU in Ningbo have evolved toward increased virulence and resistance.ConclusionThe CR-AB isolates from the ICU in Ningbo demonstrate heightened resistance and virulence traits in comparison to the CS-AB isolates. The application of the efflux pump inhibitor PAβN markedly increases the susceptibility of CR-AB to ceftazidime/avibactam.